Repeated job quits: stepping stones or learning about quality? - Anne C. Gielen (Institute for the Study of Labor (IZA), 2008)
Despite the fact that worker quits are often associated with wage gains and higher overall job satisfaction, many workers quit once again within one or two years after changing jobs initially. Such repeated job quit behavior may arise as a stepping stone to better quality jobs (Burdett, 1978) or as a response to unexpectedly low job quality (Jovanovic, 1979). This paper tests the validity of both explanations using data from the UK labor market in order to improve our understanding of job search behavior. Results from panel estimations of job quits and job satisfaction illustrate that the labor market is characterized by elements of both explanations. More specifically, a variance decomposition shows that the stepping stone model explains 80 percent of repeated job quit behavior; the remaining 20 percent is the result of learning about job quality. Hence, workers appear to need several job quits to find their most preferred job and multiple job quits serve as a stepping stone to more satisfaction at work.
urn:nbn:de:101:1-20081127675
Keywords: J28; 330; Job search; job satisfaction; labor mobility; Arbeitsmobilität; Arbeitsuche; Arbeitszufriedenheit; Lohn; Großbritannien